Was the volcanism during the Ordovician-Silurian transition in South China actually global in extent? Evidence from the distribution of volcanic ash beds in black shales. (January 2021) - Du, Xuebin; Jia, Jixin; Zhao, Ke; Shi, Jiacheng; Shu, Yi; Liu, Zhanhong; Duan, Dan
Abstract: Whether volcanic activity in South China (SC) was synchronous with global volcanism during the Ordovician-Silurian transition (OST) has long been an interesting topic. In recent years, an increasing number of volcanic ash beds (VABs) have been identified in outcrops and individual wells, thereby providing more evidence to explore this issue. Here, we used 12 outcrops and 3 wells to investigate the VABs distribution in SC and compared it with the distribution of VABs in other parts of the world. Detailed analysis reveals that the volcanism in SC was not only a part of the global volcanic activity but also had unique characteristics. In SC, the volcanic activity may have been stronger than that in other areas, because more VABs have been discovered. Additionally, the VABs in SC primarily formed during the Late Ordovician Katian and Hirnantian stages and the early Silurian Rhuddanian stage, while in other areas, they mainly formed during the Late Ordovician Sandbian and Katian stages. These characteristics may indicate that the volcanic activity in SC occurred slightly later than that in other areas. Furthermore, the interval with a dense VAB distribution corresponds to the organic-rich shale section, indicating that volcanic activity influenced the formation of the organic-rich shale to some degree by changing the paleoproductivity and paleoredox conditions. These results provide some insight into the relationship between volcanic activity in SC and global volcanism during the OST, and information on the impact of volcanic activity on the formation of organic-rich shale. Graphical abstract: Image 1 Highlights: Volcanic activity in Ordovician-Silurian transition was a major important geological event. Volcanic activity in SC occurred slightly later and was more intense than that in other areas. Volcanic activity had a certain influence on organic-rich shale.